Economic Feasibility Analysis of The Construction of The Tanjung Kramat (HM. Agus) Road Section of East Kutai District - Tukimun, Tukimun; Marzuki, Robby; Anggraeny, Devita Rizky (LPPM of NAROTAMA UNIVERSITY, 2024)
Road construction is very much needed in an effort to improve the regional economy, open access to the distribution of goods/services & people as well as in regional development efforts. This activity requires technical and economic planning to ensure that the activity is feasible to carry out. For this reason, it is necessary to conduct an analysis of the economic feasibility of constructing the Tanjung Keramat (HM. Agus) road in East Kutai Regency. This analysis uses the compound interest calculation method, Net Present Value (NPV) and Benefit Cost Ratio (BCR). The results obtained from the BOQ and RAB calculations showed that the total construction costs were Rp. 46,600,000,000.00. The results of the present value calculation over a 20 year life of construction costs + routine & periodic maintenance costs are Rp. 65,677,946,740.00. The results of calculating the benefits of Vehicle Operational Costs (BOK) for BENEFITS' current value are IDR 276,921,095,567.00. The results of the economic feasibility are declared